A PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR NEGERI 124 PALEMBANG - Setiawan, Andika; Marhamah; Kuswidyanarko , Arief (Universitas Veteran Bangun Nusantara, 2024)
This research aims to determine the significant influence in student learning outcomes between class IV.B as the control class and class IV.C as the experimental class which uses audio-visual media at SDN 124 Palembang. This research used a True Experimental treatment design. The research population was all fourth grade students at SD Negeri 124 Palembang, totaling 105 students for the 2023/2024 academic year. The sampling technique used is random sampling. Instrument validity, the test was tested using the Product Moment Person correlation formula and to determine its reliability it was tested using the Cronbach's Alpha method. The data analysis technique uses the t test (Independent Sample T-Test), whose normality and homogeneity have previously been determined. The results of the experimental group's research obtained an average score of 78.6 and the control group obtained an average posttest score of 69.86, so it can be concluded that there is a significant influence on student learning outcomes in class IV mathematics learning on mathematics sentences and calculations at SDN 124 Palembang in the even semester of the 2023/2024 academic year.